TREATMENT OF TEXTILE WASTEWATER USING A CONTINUOUS FLOW ACTIVATED SLUDGE SYSTEM AT PILOT-SCALE - M. A. ABOULHASSAN; S. SOUABI; H. EL OUARGHI; M. A. BAHLAOUI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Textile industry wastewaters contain high concentrations of organic matter, toxic substances and dyes and pigments, and are harmful to receiving environment. Activated sludge system at pilot scale with continuous feeding, was used for the treatment of a dyeing unit effluent. The results showed that treatment allows a removal rate of 40-56 % of chemical oxygen demand (COD), and 13 to 30 % of color. The adsorption on sludge appears to be the main process responsible for the color removal of wastewater generated by textile industry.